Dimerized, buckled, or ideal chains on the diamond (111)2 × 1 surface? - Schmidt, Wolf Gero; Scholze, A.; Bechstedt, F. (Surface Science)

Czermak, Johannes (Hg.), Philosophy of Mathematics. Proceedings of the 15th International Wittgenstein-Symposium, 16–23 August 1992, Kirchberg am Wechsel, Austria, Part 1, Hölder-Pichler-Tempsky: Wien 1993 (= Schriftenreihe der Wittgenstein-Gesellschaft; 20/I) [Zbl. 0836.00022] - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

MacLane, Saunders, “The Protean Character of Mathematics”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [ Zbl 0839.00019], 1–13 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Erwerbssituation, mentale Repräsentation und sprachliche Lokalisationen - Blickpunktinformation als Bestandteil der Raumrepräsentation - Buhl, Heike M. (Sprache und Kognition)
Explored the question of point of view as a part of the mental representation of space. Human Ss: 80 normal German adults (university students) (Exp 1). 48 normal German adults (university students) (Exp 2). Ss participated in 2 separate experiments in which spatial expressions were taken to indicate the point of view in mental representation and in which one object was localized within a route direction context. Results were discussed as to whether working memory load offers an explanation for the availability of viewpoint oriented information that allows for changes in mentally represented point of views.

Forumsbeitrag: Bericht über das Münchner Graduiertenkolleg Geschlechterdifferenz und Literatur - Öhlschläger, Claudia (Der Deutschunterricht 1/1996: Differenzen - diesseits und jenseits von Geschlechterfixierungen (Hg.) Eva Kublitz-Kramer und Eva Neuland)

Chirped fiber Bragg gratings for optical dispersion compensation: How to improve their fabrication accuracy - Sandel, D; Noé, Reinhold (22ND EUROPEAN CONFERENCE ON OPTICAL COMMUNICATIONS, PROCEEDINGS, VOLS 1-6: CO-LOCATED WITH: 2ND EUROPEAN EXHIBITION ON OPTICAL COMMUNICATION - EEOC ‘96)

Analyses of Sub 1/4-Micron MOS-Transistors by Visible Light Emission - Muller, J.; Wirth, G.; Hilleringmann, Ulrich; Goser, K. (ESSDERC ’96: Proceedings of the 26th European Solid State Device Research Conference)

On the Observability of dynamic localization in semiconductor superlattices using optical spectroscopy - Meier, Torsten; Rossi, F.; Je, K.-C; Hader, J.; Thomas, P.; Koch, S.W. (Hot Carriers in Semiconductors)
During the last decade, a variety of field-induced coherent phenomena in semiconductor superlattices has received considerable attention both from a theoretical and from an experimental point of view. For the case of a static applied electric field, the existence of Bloch oscillations has been predicted theoretically and confirmed by means of different experimental techniques of nonlinear optical spectroscopy.

Field-induced exciton ionization studied by four-wave mixing - Meier, Torsten; Koch, M.; von Plessen, G.; Feldmann, J.; Koch, S.W.; Thomas, P.; Göbel, E.O.; Goosen, K.W.; Kuo, J.M.; Kopf, R.F. (Hot Carriers in Semiconductors)
The dynamics of carriers induced by electric fields in semiconductor superlattices has received much interest in recent years. Phenomena like Bloch oscillations and negative differential velocity in these structures have been studied using a variety of experimental techniques [1–5]. One particular point of interest has been the transition of the miniband regime to the Bloch oscillation regime with increasing electric field [6,7]. Cw spectra of strongly-coupled superlattices have evidenced that this transition is concomitant with a rapid field-induced ionization of the zero-field miniband exciton [5,8]. While it has been pointed out from the theoretical side that the field-induced ionization process strongly influences the coherent dynamics in the transition region [9], no systematic experimental investigation of the ionization process has been carried out so far. One interesting question that such an investigation could help to answer is to what extent this ionization process differs from the well-documented case of field-induced exciton ionization in bulk semiconductors.

Phonon-Induced Suppression of Bloch Oscillations in Semiconductor Superlattices: a Monte Carlo Investigation - Meier, Torsten; Rossi, F.; Thomas, P.; Koch, S.W.; Selbmann , P.E.; Molinari, E. (Hot Carriers in Semiconductors)
The progress in the generation of ultrashort laser pulses, together with the development of spectroscopies on this time-scale, has led to a series of experiments which give new insight into the microscopic carrier dynamics in semiconductors. In particular, the energy relaxation of photoexcited carriers has been widely investigated. At the same time, recent progress in the fabrication and characterization of semiconductor heterostructures and superlattices allows a detailed study of a new class of phenomena induced by an applied electric field, such as Bloch oscillations1,2. Both classes of phenomena typically occur on a pico- or femtosecond time-scale, where the coupling between coherent and incoherent phenomena is known to play a dominant role3. Therefore, an adequate theoretical model of the ultrafast dynamics on this time-scale must account for both coherent and incoherent effects on the same kinetic level.

Eine Bibliothek von Basisdiensten für Parallelrechner: Routing, Synchronisation, gemeinsamer Speicher - Wachsmann, Alf

Existenzgründung - Kremer, H.-Hugo (Meisterprüfung - Lernen für die Praxis - Unternehmensführung 1)

Existenzgründung - Kremer, H.-Hugo (Meisterprüfung - Lernen für die Praxis - Unternehmensführung 1)

Continuous speech dictation - From theory to practice - Steinbiss, Volker; Ney, Hermann J.; Essen, Ute; Tran, Bach Hiep; Aubert, Xavier L.; Dugast, Christian; Kneser, Reinhard; Meier, Hans Günter; Oerder, Martin; Haeb-Umbach, Reinhold; Geller, Dieter; Hoellerbauer, W.; et al. (Speech Communication)
This paper gives an overview of the Philips research system for phoneme-based, large-vocabulary, continuousspeech recognition. The system has been successfully applied to various tasks in the German and (American) English languages, ranging from small vocabulary tasks to very large vocabulary tasks. Here, we concentrate on continuousspeech recognition for dictation in real applications, the dictation of legal reports and radiology reports in German. We describe this task and report on experimental results. We also describe a commercial PC-based dictation system which includes a PC implementation of our scientific recognition prototype. In order to allow for a comparison with the performance of other systems, a section with an evaluation on the standard Wall Street Journal task (dictation of American English newspaper text) is supplied. The recognition architecture is based on an integrated statistical approach. We describe the characteristic features of the system as opposed to other systems: 1. the Viterbi criterion is consistently applied both in training and testing; 2. continuous mixture densities are used without tying or smoothing; 3. time-synchronous beam search in connection with a phoneme look-ahead is applied to a tree-organized lexicon.

Quasi-particle band structure of C(111)2 × 1 and C(100)2 × 1 surfaces - Kress, Clemens; Fiedler, Marion; Schmidt, Wolf Gero; Bechstedt, Friedhelm (Surface Science)

III-V(110)/Sb(1 ML): structural and dynamical properties - Schmidt, Wolf Gero; Srivastava, G.P. (Surface Science)

A Formal Definition of an Abstract VHDL'93 Simulator by EA-Machines - Börger, Egon; Glässer, Uwe; Müller, Wolfgang (Semantics of VHDL)
We present a rigorous but transparent semantic definition for VHDL corresponding to the IEEE VHDL’ 93 standard [68, 9, 84]. Our definition covers the full behavior of signal and variable assignments as well as the behavior of the various wait statements including delta, time, and postponed cycles. We consider explicitly declared signals, ports, local variables, and shared variables. Our specification defines an abstract VHDL ’ 93 interpreter in the form of transition rules for an evolving algebra machine (EA-Machine) [60]. It faithfully reflects and supports the view of simulation given in the IEEE VHDL ’ 93 standard language reference manual. The definition can be understood without any prior formal training. We illustrate our definition by running the example VHDL program set out in the Introduction to this volume.
Keywords: Transition Rule Formal Verification Variable Assignment Kernel Process Simulation Cycle

Quantum beats from biexcitons in narrow quantum wells: polarization and density dependence - Meier, Torsten; Albrecht, T.F.; Schulze, A.; Koch, M.; Bott, K.; Feldmann, J.; Stolz, W.; Kuhl, J.; Mayer, E.J.; Koch, S.W.; Göbel, E.O.; Cundiff, S.T. (Quantum Electronics and Laser Science Conference)
Transient four-wave mixing (TFWM) has been extensively used during the last few years to study exciton dynamics in semiconductors and in semiconductor heterostructures. These studies have provided significant insight into exciton dynamics in both ordered and disordered systems. There are, nevertheless, still certain aspects of the excitonic TFWM response that are not completely understood. In particular, a complete understanding of the polarization and intensity dependences of the signai strength, the decay of the time-integrated signal, and the temporal characteristics of the time-resolved signal has proven elusive. Recent theoretical and experimental work has indicated that exciton-exciton interactions are important.1·2 Such interactions include incoherent processes, such as excitation-induced dephasing, and the formation of biexcitons. Additionally, some of the phenomena result from disorder, making them sample dependent.

Polarization dependence of quantum beats between light-hole and heavy-hole excitons in GaAs quantum wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Bott, K.; Heuckeroth, V.; Thomas, P.; Koch, M.; Hey, R.; Ploog, K. (Quantum Electronics and Laser Science Conference)
The appearance of quantum beats (QBs) between heavy-hole (hh) and light-hole (lh) excitons in GaAs quantum wells (QWs) has been observed in many degenerate-four- wave-mixing (DFWM) experiments with subpicosecond optical pulses. Although the variation of the beat amplitude and phase with polarization of the incident pulses was recognized early on, a consistent theoretical interpretation of exciton coherence for the case of simultaneous excitation of hh and lh excitons is still missing.

Berücksichtigung von Datenschutzaspekten in einem bevölkerungsbezogenen Krebsregister - Thoben, Wilfried; Appelrath, Hans-Jürgen; Rettig, Jens; Sauer, Stefan (Proceedings of the conference on Medizin und Information, Biometrie und Epidemiologie (GMDS 1994), Dresden (Germany))
Die Pilotphase 1993/ 94 zum Aufbau eines Niedersächsischen Krebsregister untersucht das im Entwurf des Bundeskrebsregistergesetzes vorgesehen Modell für ein bevölkerungsbezogenes Krebsregister. Darin werden die Krebsmeldungen in einer Vertrauensstelle erfaßt und die personenidentifizierenden Daten vor der Übermittlung an die Registerstelle anonymisiert, wo sie dann zu einem bevölkerungsbezogenen Krebsregister verdichtet und epidemiologischer Forschung zur Verfügung gestellt werden ([1], [2], [3]). Dieses sogenannte „Michaelis“-Modell erlaubt eine bevölkerungsbezogene Registrierung von Krebsfällen unter Berücksichtigung datenschutzrechtlicher Aspekte („Informationelles Selbstbestimmungsrecht“) der einzelnen Betroffenen. In vier Teilprojekten werden dabei in der Modellregion Weser-Ems die Integration krebsregistrierender Einrichtungen, die Chiffrierung/ Dechiffrierung von Krebsmeldungen, der Abgleich anonymisierter Meldungen in der Registerstelle und die Entwicklung eines epidemiologischen Informationssystem betrachtet ([4], [5]).